Remaining challenges in cellular flavin cofactor homeostasis and flavoprotein biogenesis - Giancaspero, Teresa A.; Colella, Matilde; Brizio, Carmen; Difonzo, Graziana; Fiorino, Giuseppina M.; Leone, Piero; Brandsch, Roderich; Bonomi, Francesco; Iametti, Stefania; Barile, Maria (Frontiers in Chemistry, 2015)
The primary role of the water-soluble vitamin B2 (riboflavin) in cell biology is connected with its conversion into FMN and FAD, the cofactors of a large number of dehydrogenases, oxidases and reductases involved in energetic metabolism, epigenetics, protein folding, as well as in a number of diverse regulatory processes. The problem of localisation of flavin cofactor synthesis events and in particular of the FAD synthase (EC 2.7.7.2) in HepG2 cells is addressed here by confocal microscopy in the frame of its relationships with kinetics of FAD synthesis and delivery to client apo-flavoproteins. FAD synthesis catalysed by recombinant isoform 2 of FADS occurs via an ordered bi-bi mechanism in which ATP binds prior to FMN, and pyrophosphate is released before FAD. Spectrophotometric continuous assays of the reconstitution rate of apo-D-aminoacid oxidase with its cofactor, allowed us to propose that besides its FAD synthesising activity, hFADS is able to operate as a FAD "chaperone". The physical interaction between FAD forming enzyme and its clients was further confirmed by dot blot and immunoprecipitation experiments carried out testing as a client either a nuclear or a mitochondrial enzyme that is lysine specific demethylase 1 (LSD1, EC 1.-.-.-) and dimethylglycine dehydrogenase (Me2GlyDH, EC 1.5.8.4), respectively which carry out similar reactions of oxidative demethylation, assisted by tetrahydrofolate used to form 5,10-methylene-tetrahydrofolate. A direct transfer of the cofactor from hFADS2 to apo-dimethyl glycine dehydrogenase was also demonstrated. Thus, FAD synthesis and delivery to these enzymes are crucial processes for bioenergetics and nutri-epigenetics of liver cells.